Liquid Propane Injection in Flash-Boiling Conditions - Łukasz Jan Kapusta; Jakub Bachanek; Changzhao Jiang; Jakub Piaszyk; Hongming Xu; Mirosław Lech Wyszyński (Energies, 2021)
This study aimed to investigate the influence of flash-boiling conditions on liquid propane sprays formed by a multi-hole injector at various injection pressures. The focus was on spray structures, which were analysed qualitatively and quantitatively by means of spray-tip penetration and global spray angle. The effect of flash boiling was evaluated in terms of trends observed for subcooled conditions. Propane was injected by a commercial gasoline direct injector into a constant volume vessel filled with nitrogen at pressures from 0.1 MPa up to 6 MPa. The temperature of the injected liquid was kept constant. The evolution of the spray penetration was observed by a high-speed camera with a Schlieren set-up. The obtained results provided information on the spray evolution in both regimes, above and below the saturation pressure of the propane. Based on the experimental results, an attempt to calibrate a simulation model has been made. The main advantage of the study is that the effects of injection pressure on the formation of propane sprays were investigated for both subcooled and flash-boiling conditions. Moreover, the impact of the changing viscosity and surface tension was limited, as the temperature of the injected liquid was kept at the same level. The results showed that despite very different spray behaviours in the subcooled and flash-boiling regimes, leading to different spray structures and a spray collapse for strong flash boiling, the influence of injection pressure on propane sprays in terms of spray-tip penetration and spray angle is very similar for both conditions, subcooled and flash boiling. As for the numerical model, there were no single model settings to simulate the flashing sprays properly. Moreover, the spray collapse was not represented very well, making the simulation set-up more suitable for less superheated sprays.